Neurological Implications of Non-critically Ill Patients With Coronavirus Disease 2019 in a Fangcang Shelter Hospital in Wuhan, China - Yan, Nao; Xu, Zhipeng; Mei, Bin; Gao, Yongzhe; Lv, Dongwei; Zhang, Junjian (Frontiers in Neurology, 2020)
Background: Coronavirus disease 2019 (COVID-19) is a new viral respiratory disease and has become a pandemic. Fever, weakness, and dry cough are the main clinical manifestations. However, little is known about neurological symptoms of non-critically ill COVID-19 patients. Objective: To investigate the neurological symptoms and implications of patients with non-critically ill COVID-19 patients. Materials and Methods: This retrospective cohort study investigated all COVID-19 patients admitted to Wuhan East-West Lake Fangcang shelter hospital. Demographic data, clinical manifestations, comorbidities, radiological data, the result of nucleic acid test, and treatments were collected and analyzed. Results: Among 1,682 patients with confirmed non-critically ill COVID-19, 509 patients (30.3%) had neurological symptoms, including myalgia (311, 18.5%), headache (216, 12.8%), fatigue (83, 4.9%), and dizziness (15, 0.9%). One hundred and fourteen patients (6.8%) were the expansion of pulmonary infection according to their chest CT images and medical history. Compared with patients without neurological symptoms, patients with neurological symptoms had a significantly longer length of hospital stay, time of nucleic acid turning negative, and the mean time from onset of symptom to hospital admission (p < 0.05). Patients with neurological symptoms were more likely to occur the expansion of pulmonary infection compared with the patients without neurological symptoms (46/509 [9.0%] vs. 68/1,173 [5.8%]). Conclusions: Non-critically ill COVID-19 patients commonly have neurological symptoms. Neurological symptoms are significantly associated with the processes of COVID-19. Early identification and aggressive treatment are particularly important for COVID-19 patients with neurological symptoms.